IDENTITY OF THE ACEHNESE SOCIETY IN THE COMMERCIAL DIASPORA OF GROCERY STORE IN MALAYSIA - Ichsan, Muhammad (International Review of Humanities Studies, 2021)
This journal contains the identity of the Aceh people in diaspora of grocery store (Kedai Runcit) in Malaysia. Diaspora plays a role in the establishment of a cosmopolitan commercial culture. The spread of humans from various parts of the earth to other parts of the world, meeting each other, communicating, forming networks, is ultimately a meeting between cultures, mutual appreciate, mutual respect, and mingling. Given that interaction between people is one of the important factors in strengthening relations between countries. The Indonesian diaspora is also expected to strengthen bilateral relations between Indonesia and Malaysia. The form of actualization of the runcit diaspora is a type of commerce that is easy to engage and can contribute to development. The study of these findings is focused on a review of the cultural identity of the Acehnese society in the grocery store diaspora in Malaysia. Among the Diaspora minorities in Malaysia, there are a small number of Acehnese migrants after the conflict and post-tsunami. Malaysia is known as the second multi-ethnic country after Singapore in the Southeast Asian Region. Researchers would look for samples of Acehnese people who have succeeded in creating new communities among ethnic communities, local Malays, ethnic Chinese, ethnic Indians who are the majority in Malaysia. Researchers would use the method of Literature Review and Netnography interview in data collection. The sample taken was Acehnese people who live or have a grocery store in Malaysia. The results of this research found that it is true that there is a diaspora process between the Acehnese people in Malaysia through commerce.